A Robust Absorbent Material Based on Light‐Responsive Superhydrophobic Melamine Sponge for Oil Recovery. Issue 5 (28th December 2015) - Zhu, Haiguang; Yang, Shun; Chen, Dongyun; Li, Najun; Xu, Qingfeng; Li, Hua; He, Jinghui; Lu, Jianmei
Abstract : Advanced materials with intelligent switchable surfaces that can respond to external stimuli have encouraging application in oil/water separation and oil clean‐up. Herein, a facile method has been demonstrated to prepare a robust and superhydrophobic sponge by integrating the melamine‐formaldehyde (MF) sponge with light‐responsive spiropyran derivative via a radical copolymerization process, which shows the light‐controllable oil absorption and desorption property under light illumination. The key chemistry is that the MF sponge is first modified with vinyl for the copolymerization via a facile solution‐immersion process. Afterward, light‐responsive spiropyran methacrylate monomers are copolymerized with vinyl‐modified MF sponges to fabricate polymer‐MF sponge composites (denoted as SP‐MF sponge), resulting in the wettability conversion from amphiphilic to superhydrophobic with a water contact angle of 155.5°. The superhydrophobic MF sponge shows excellent selectivity and high absorption capacity for a range of oils and organic solvents from 70 to 154 times its own weight. More importantly, since the hydrophobic polymer of the SP‐MF sponge can be converted to hydrophilic under UV illumination, the wettability of SP‐MF sponge will change to hydrophilic, resulting in the light‐controlled oil desorption process. These findings offer a new responsive absorbent material and a new approach for oil recovery. Abstract : A light‐responsive material based on melamine sponge coated spiropyran methacrylate derivative is successfully prepared for removing oil and organic solvents from water. It can switch its absorption and desorption of oil and organic solvent under light irradiation. In addition, it exhibits high absorption capacity (74–154 times its own weight) for a range of common oils and organic solvents.